Case of Teachers’ Communicative Competence Development Within the System of Methodological Work in the Context of Preschool Educational Establishments - Sergeevna Vasilyeva, Victoria; Yurievna Nikitina, Elena (International Journal of Engineering and Technology, 2018)
The urgency of the problem of communicative competence development of preschool teachers is caused by the need for constant improvement of pedagogical approaches, methods and technologies. The development of teachers’ skills in the process of continuing professional activities is crucial for meeting the modern requirements of professional standards, imposed by the society based on the recent studies on a teacher’s role in early childhood education, child-rearing and development. The article is dedicated to providing a rationale for methodological approaches to developing teachers’ communicative competence in the course of methodological work in preschool educational establishments, taking into account the personally-significant and professionally-oriented aspects. The main research technique used to study the problem is the method of participant observation. It made it possible to conduct an authentic evaluation, using the communication project method and analysis of the diagnostic study of 332 preschool teachers who took part in putting the concept of teachers’ communicative competence development in the context of systematic employment in preschools into practice. The article shows how the applied pedagogical approaches, patterns and principles of the educational process, ensure the continuing compliance with the current requirements for teachers’ level of professional training, particularly, the need for the constant development of communicative competence. The relevance of the problem is characterized by the qualitative changes in the composition of students of preschool educational establishments, constantly changing social situations, requiring prompt decision-making, aimed at ensuring the most comfortable, safe and progressive conditions for the younger generation. The article presents the results of the practical application of the proposed theoretical and methodological approaches, based on the pedagogical patterns and principles governing the development of teachers’ communicative competence within the scope of preschool educational establishments. The result of the study is an elaborate set of methodological approaches, pedagogical patterns and principles working towards developing teachers’ communicative competence at the general-theoretical, empirical and methodological-technological levels. The materials of the article can be of practical value for students and instructors of pedagogical and humanities universities, people in charge of curriculum and discipline at preschool educational establishments, whose job is to address the issues that preschool teachers face within the boundaries of continuing vocational education.